Infographic impact on the development of academic achievement in a computers first secondary students Al Qunfudhah - Shawoush, Mohammed Abdullah Mohammed (Journal of Educational and Psychological Sciences, 2019)
The research aimed to identify the effect of the using infographics on developing academic achievement in computer subject of First Grade Secondary School students in Al-Qunfudah Governorate. To achieve this goal, the experimental method was used in terms of adopting the quasi-experimental design. The researcher prepared an achievement test on computer. A pre-post test was applied to a random sample of 60 students from First Grade Secondary School students in Al-Qunfudah Governorate. The sample was divided into two equivalent groups. One was experimental, (30) students, who studied using infographics, and the other 30 students, who studied using the usual method. The results of the study revealed that there are statistically significant differences at (0.05) level between the average scores of the students in the experimental and control groups. The experimental group achieved a total average of (37) whereas the control achieved a total average of (25.07) in the post application of the achievement test, and the difference is in favour of the experimental group. The results showed a significant effect of the use of the infographics on the development of the academic achievement of the experimental group. The value of ETA Square (45,0). This means that the independent variable has a (large) effect. In the light of these results, the researcher made some recommendations and suggestions.
Keywords: infographics; academic achievement; computer subject; first secondary school; Al-Qunfudhah Governorate